HISTORY AND MODERNITY OF LOCAL SELF-GOVERNMENT - Borodin, Ivan; Myronets, Oksana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: of the article is to consider the historiography of local self-government and analysis of scientific constructions to find its basic elements that could be accepted to create an optimal model of this institution in Ukraine and the introduction of progressive approaches to statehood in Ukraine. Research methods: historical, phenomenological, comparative-legal, sociological, formal-logical, dialectical. Results: the proposed analysis of the history of local self-government, its understanding by different scientists, representatives of different scientific schools, should serve the development of scientific thought in a given paradigm, become, as appropriate, the basis for the further development and improvement of legislation defining and regulating local government as a state institution, as a sign of mature democracy and civil society. Discussion: the issue of local self-government attracts the attention of legal science. This is due to the fact that as society develops, the issues of improving the efficiency and democratization of public administration begin to be increasingly important. The proclamation of Ukraine’s independence contributed to the intensification of the process of democratization of our society and our state. An important part of this process is represented by the building an optimal system of local self-government in Ukraine, which in the modern world is perceived as the only possible democratic and rational model of local government, one of the integral attributes of our civil society.